Car Boot Sale open up 2017 Career Fair - Thulashi, Murugayah (2017)
Universiti Malaysia Pahang organised a sales carnival as part of promotion for Open Interview Program Eastern Zone that will be held on 29 and 30 March. This program will see the involvement of more than 150 companies that will be offering 25,000 vacancy in various position and also place for industrial training.